Wages and Benefits in the Florida Landscape Industry - Alan W. Hodges; John J. Haydu (EDIS)
FE788, a 9-page illustrated report by Alan W. Hodges and John J. Haydu, reports the results of a study to document current compensation, benefits, and employment practices in the landscape industry in Florida, through a representative survey sample. Includes references. Published by the UF Department of Food and Resource Economics, December 2008.